2019
DOI: 10.7717/peerj.7465
|View full text |Cite
|
Sign up to set email alerts
|

The effect of platelet lysate in culture of PDLSCs: anin vitrocomparative study

Abstract: Background Cellular therapy clinical applications require large-scale production of stem cells. Therefore, abundance, ease of isolation, and proliferative potential are the most important factors in choosing the appropriate source of cells for transplantation studies. Multipotent stem cells obtained from periodontal ligament (PDL) can be used in periodontal tissue regeneration. In this study, we aimed to evaluate and compare the characteristics of periodontal ligament stem cells (PDLSCs), extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
(67 reference statements)
1
6
0
Order By: Relevance
“…While high concentration 20 mg/mL resulted in a reduction of cell growth leading to an increase in cell death percentages, compared to the low concentrations. These data are consistent with previously published data [31,32,35].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…While high concentration 20 mg/mL resulted in a reduction of cell growth leading to an increase in cell death percentages, compared to the low concentrations. These data are consistent with previously published data [31,32,35].…”
Section: Discussionsupporting
confidence: 94%
“…As previously described [31], 1 × 10 5 cells/well were cultured in 6 well plates, with culture medium and allowed to reach complete confluent monolayer. Before wound infliction, starvation media without serum were added to hPDLSCs and incubated for 24 h. Then, a wound (scratch) was inflicted by using 200 µL pipette tip, through 100% confluent cells followed by a washing step with phosphate buffered saline (PBS) to remove cell debris.…”
Section: Wound Healing Assay (Scratch Assay)mentioning
confidence: 99%
“…This freeze-thaw method for platelet activation; following a high-speed centrifugation and supernatant abstraction, a leucocyte-free PL was obtained. Numerous studies have demonstrated the positive effects of PL products in tissue culture and clinical settings 25 26 27 28 29 30 . These clinical trials have illustrated favourable PL clinical outcomes in different diseases such as lateral epicondylitis, knee osteoarthritis and lumbar radicular pain 28 29 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The outgrowth method has been suggested to outperform enzymatic digestion in terms of efficiency and preservation of the commitment capacity regarding both the formation of mineralized nodules and the expression of cementoblast-like genes [ 28 ]. Consistently, the paper by Abuarqoub et al compared the features of PDLSCs expanded using either fetal bovine serum (FBS) or platelet lysate (PL) and concluded that the latter outperformed the former [ 29 ].…”
Section: The Role Of Pdl Cellsmentioning
confidence: 90%